Industrial safety practices as determinants of employees' performance and wellbeing at selected industries in Port- Harcourt, River state, Nigeria (2012)
"It makes good business sense to promote industrial safety issues and programs at the workplace in order to enhance workers' performance and wellbeing. It is against this background that this study looked at the involvement of industrial safety practices on employees' performance and wellbeing. The descriptive survey research design was adopted for the study. Three hundred and twenty respondents were randomly selected from five industries that had records of safety practices. Six questionnaires were used to collect data and the analyses were done at a = 0.05 level. Findings showed that staff training, recruitment of skilled personnel, evaluation of safety performance and rewards/safety incentives correlated significantly with performance and wellbeing, but selection of personnel and evaluation of safety performance did not correlate with wellbeing significantly. It was recommended that social workers should work with both employers and employees to see to the explanation of causative mechanism for injuries rather than proximal causes. "